DATACENTER TEMPERATURE MONITORING SYSTEM BASED ON INTERNET OF THINGS - Escola, João Paulo Lemos; Freitas, Jovander da Silva (Revista Interface Tecnológica, 2020)
The data stored in the company’s datacenter is crucial and is part of its assets. The forms of camera bus constantly guarantee the security of data and equipment installed in the datacenter environment. An efficient temperature control with the use of air conditioners is also important for the manager. This work presents a solution for temperature control of the datacenter, allowing the manager an additional resource that allows to decrease the workload, being notified in case of failure in the cooling of the environment, allowing the use and the useful life of the equipment present in the datacenter. Using the Orange Pi microcontroller, temperature capture module, an efficient algorithm and email alerts, its use is ten times less than the market applications.